Evaluating the Usability of a Next-Generation Heads-Up Display for Firefighters in a Virtual Environment. (September 2022) - Saville, Jason D.; Spain, Randall D.; Slack, Donia; Hill, Edward; Lester, James
Virtual environments provide a rich and immersive platform to investigate how interfaces should be designed to support public safety operations. Virtual environments can be used to simulate the tasks, demands, and conditions of emergency response events while providing a controlled and safe environment for testing and developing new user interface capabilities. This paper presents an evaluation of a prototype AR-based heads-up display (HUD) that was integrated in a desktop-based virtual environment that simulated an emergency response scenario. Members of the first responder community (N = 90) completed a series of emergency response tasks and responded to a series of usability and user experience questions and workload ratings. The study used a 2 (Condition: HUD vs. No HUD) x 2 (Task Load: Radio monitoring task vs. No radio monitoring task) mixed experimental design. Participants provided very positive feedback on the utility of the prototype HUD for supporting task performance. Results and future research plans are discussed.